(3CSGei GdCSO hcfGgs - (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj, J (B650 (3g` s
(3ChdgG (B:s
(3bGd gPG eNJUQ LeYJg ai CSGei GdCSO hcfGg eQJHI Ydi MQha GdeYLe , hLYdJg KeGfjI aUhd , GdaUd GdChd ai CSeGA GdCSO , GdaUd GdKGfi cfGg , GdaUd GdKGdK ai fYhJI hGdbGHI s
(3BNQgG (B:s
(3hGdUhJ cSQg GdYXGe GdYVYVI hGdQhKg GdYWQe GdaUd GdKGef ai GdeCSOI efgG HjTI GdTQi BNQ CSeGA GdCSO hcfGg s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH (B1852) s
Keywords: (3GddZIs